Analysis Of The Head Loss Phenomenon Values In Straight Pipelines With Silica Sand Variations As Filtration - Ibnu Irawan (Universitas Trunojoyo Madura, 2022)
In this reseaerch, the tool design and analysis of the head loss phenomenon in the filtration sys- tem experiment was done to determine the effect of head loss caused by variations in silica sand and silica sand composition. This design was also made to determine the performance of the head loss experimental device on the filtration system. Head loss is a loss of pressure caused by fluid friction in the pipe, or it can also be caused by changes in the shape and dimensions of the pipe, such as in pipe joints. In this design, most use sand as one of the main filter media, with 3 variations of Very Fine sand 0.05-0.1mm, Medium 0.1-0.25mm, Coarse 0.5-1.0mm, and 3 various compositions PS 50% KA 50%, PS 70% 30%, PS 80% 20%. In designing the head loss test channel using a variation of filtration to know the value of head loss in the filtration system, a digital water meter to measure the water discharge is used to measure the pressure at the inlet (á¹in) and pressure at the outlet (á¹out). This tool is also designed in a modular way (disassembly), where in the experiment varia- tion and without filtration can be used interchangeably. Experiments carried out using filtration produced an average theoretical value on the composition of PS 50% KA 50% sand with a variation of Very Fine silica sand 0.05 â€“ 0.1 mm smaller than the composition of PS 70% KA 30% and PS 80% KA 20% with a variation of Very Fine silica sand 0.05 â€“ 0.1 mm and a variation of Very Coarse silica sand 0.5 â€“ 1.0 mm. Meanwhile, the higher headloss value shows the composition of PS 50% KA 50% with variations of Very Coarse Silica Sand 0.5 â€“ 1.0 mm. 3) In the data collection experi- ment using the Design Of Experiment (DOE) Factorial, the P-Value for Composition was 0.965 0.05 indicating an insignificant condition and the P-Value for Sand 0.006 0.05 indicated a signifi- cant condition. The factorial chart shows the condition that sand (B) greatly influences the occur- rence of head loss in water flow.